A fundamental conflict of care: Nurses' accounts of balancing patients' sleep with taking vital sign observations at night. Issue 9 (12th March 2018) - Hope, Joanna; Recio‐Saucedo, Alejandra; Fogg, Carole; Griffiths, Peter; Smith, Gary B; Westwood, Greta; Schmidt, Paul E
Abstract : Aims and objectives: To explore why adherence to vital sign observations scheduled by an early warning score protocol reduces at night. Background: Regular vital sign observations can reduce avoidable deterioration in hospital. early warning score protocols set the frequency of these observations by the severity of a patient's condition. Vital sign observations are taken less frequently at night, even with an early warning score in place, but no literature has explored why. Design: A qualitative interpretative design informed this study. Methods: Seventeen semi‐structured interviews with nursing staff working on wards with varying levels of adherence to scheduled vital sign observations. A thematic analysis approach was used. Results: At night, nursing teams found it difficult to balance the competing care goals of supporting sleep with taking vital sign observations. The night‐time frequency of these observations was determined by clinical judgement, ward‐level expectations of observation timing and the risk of disturbing other patients. Patients with COPD or dementia could be under‐monitored, while patients nearing the end of life could be over‐monitored. Conclusion: In this study, we found an early warning score algorithm focused on deterioration prevention did not account for long‐term management or palliative care trajectories. Nurses were therefore less inclined to wake such patients to take vital sign observations at night. However, the perception of widespread exceptions and lack of evidence regarding optimum frequency risks delegitimising the early warning score approach. This may pose a risk to patient safety, particularly patients with dementia or chronic conditions. Relevance to clinical practice: Nurses should document exceptions and discuss these with the wider team. Hospitals should monitor why vital sign observations are missed at night, identify which groups are under‐monitored and provide guidance on prioritising competing expectations. early warning score protocols should take account of different care trajectories.